Differential expression of Annexin 2, SPINK1, and Hsp60 predict progression of prostate cancer through bifurcated WHO Gleason score categories in African American men. Issue 11 (22nd April 2018) - Beyene, Desta A.; Naab, Tammey J.; Kanarek, Norma F.; Apprey, Victor; Esnakula, Ashwini; Khan, Farahan A.; Blackman, Marc R.; Brown, Collis A.; Hudson, Tamaro S.
Abstract : Background: Although studies have observed several markers correlate with progression of prostate cancer (PCa), no specific markers have been identified that accurately predict the progression of this disease, even in African American (AA) men who are generally at higher risk than other ethnic groups. The primary goal of this study was to explore whether three markers could predict the progression of PCa. Method: We investigated protein expression of Annexin 2 (ANX2), serine peptidase inhibitor, kazal type 1(SPINK1)/tumor‐associated trypsin inhibitor (TATI), and heat shock protein 60 (Hsp60) in 79 archival human prostate trans‐rectal ultrasound (TRUS) biopsy tissues according to a modified World Health Organization (WHO) classification: normal (WHO1a), Gleason Score (GS6 (WHO1b), GS7 subgroups (WHO2 = 3 + 4, WHO3 = 4 + 3), GS8 (WHO4), and GS9‐10 (WHO5). AA men aged 41‐90 diagnosed from 1990 to 2013 at Howard University were included. Automated staining assessed expression of each biomarker. Spearman correlation assessed the direction and relationship between biomarkers, WHO and modified WHO GS, age, and 5‐year survival. A two‐tailed t ‐test and ANOVA evaluated biomarkers expression in relationship to WHO normal and other GS levels, and between WHO GS levels. A logistic and linear regression analysis examined the relationship between biomarker score and WHO GS categories. Kaplan‐Meier curves graphed survival. Results: ANX2 expression decreased monotonically with the progression of PCa while expression of SPINK1/TATI and Hsp60 increased but had a more WHO GS‐specific effect; SPINK1/TATI differed between normal and GS 2‐6 and HSP60 differed between GS 7 and GS 2‐6. WHO GS was found to be significantly and negatively associated with ANX2, and positively with SPINK1/TATI and Hsp60 expression. High SPINK1/TATI expression together with the low ANX2 expression at higher GS exhibited a bi‐directional relationship that is associated with PCa progression and survival. Conclusion: Importantly, the data reveal that ANX2, and SPINK1/TAT1 highly associate with WHO GS and with the transition from one stage of PrCa to the next in AA men. Future research is needed in biracial and larger population studies to confirm this dynamic relationship between ANX2 and SPINK1 as independent predictors of PCa progression in all men.